Effects of Copper Chloride and Lead Chloride on Different Organs (Ovary, Liver, Intestine and Gills) in Female Climbing Perch (Anabas. testudineus) - WasanAbdulmunem Taha, Syakirah Samsudin,ShathaHazem Shakir,and Huda Ayad Hameed (International Journal of Advanced Science and Technology, 2020)
testudineus is increasingly recognized as a species with nutraceutical potential, due to its high content of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA).In addition; it contains high protein content, omega-3, and omega 6. The purpose of this study was to evaluate theCuCl2 (1.5 mg/kg) and PbCl2 (2mg/kg) on the ovary, liver, intestine, and gills in female climbing perch A. testudineus, after exposure to copper and lead chloride, for 35 days. The results of this study showed that exposure to CuCl2 and PbCl2 led to Many histological changes were observed in the tissues sampled from the ovaries, liver, intestine, and gills such as cellular bulging, swelling, and necrosis, moreover, the cells lost its appearance,  difficulty identifying cells and nuclei; presence large gaps and pores. The study concluded that exposure of female A. testudineus to heavy metals led to impact significant changes in structure of tissues. The data obtained can be used to reduce the impact of heavy metals on fish physiology.